ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI UNTUK MENENTUKAN HARGA JUAL CV. VIO INDONESIA DALAM MENINGKATKAN PROFITABILITAS USAHA - Chairil Anwar; Ayu Widayati (Bajang Institute, 2023)
This research was conducted to obtain concrete evidence of the calculation of the cost of goods manufactured in determining the selling price according to company calculations by comparing the full costing method and variable costing. The validity of the research data used technical triangulation. The research method used was interview, observation, and documentation. While the type of data used is descriptive qualitative data with data analysis carried out through three stages, namely data reduction, data presentation, and drawing conclusions. The data source used is recording the calculation of costs incurred during production, then the calculation of the selling price of the product is obtained. Judging from the calculations applied by the company, the results have not been optimal, so that the owner of the company will be better off using calculations using the more accurate full costing method.